The Role of Dividend Policy in Mediating Fundamental Factors Toward Stock Prices - Ani Nurfajri; Dewi Melinda Fitri; Nurhana Dhea Parlina (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This research has the objectives to ascertain the impact of profitability, leverage, and company size on stock prices, with dividend policy serving as a mediator. This research adopts a causal associative approach employing quantitative research methods. The population for this research comprises 70 companies listed on the LQ45 index of the Indonesia Stock Exchange (BEI) from 2018 to 2022. Sampling was conducted using purposive sampling based on specific criteria, resulting in 16 samples with a total of 80 observation data points. The data analysis employed panel data multiple linear regression method utilizing the Eviews 13 application. Intervening variable testing was conducted using the Sobel test. The research findings indicate that profitability and leverage do not significantly affect dividend policy, whereas firm size significantly influences dividend policy. Additionally, profitability, leverage, and dividend policy significantly influence stock prices. On the other hand, firm size does not significantly affect stock prices. However, the analysis of indirect effects shows that dividend policy does not mediate the relationship between profitability and leverage to stock price. Instead, dividend policy serves as a mediator between firm size and stock price.